Further improvement after 24-month treatment with teduglutide in a patient with active Crohn’s disease and short bowel syndrome - Borghini, Raffaele; Caronna, Roberto; Corazziari, Enrico Stefano; Picarelli, Antonio (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Borghini R, Caronna R, Corazziari ES, Picarelli A. Further improvement after 24-month treatment with teduglutide in a patient with active Crohn’s disease and short bowel syndrome. Turk J Gastroenterol 2018; 29: 250-1.